Criminal Sanctions for Extortionists in the Perspective of Positive Law and Islamic Criminal Law: A Comparative Analysis - Zulfahmi, Zulfahmi; Hasibuan, Affan Muhammad; Pebriyanti, Pebriyanti; Nasution, Abdul Haris; Asrofi, Asrofi (al-Rasῑkh: Jurnal Hukum Islam, 2025)
Illegal levies (extortion) are a form of corruption that harms the public and weakens trust in public institutions. This research aims to analyze criminal sanctions against extortionists in the perspective of positive law and Islamic criminal law and compare their approaches. The research method uses a qualitative approach through literature study of legal literature, regulatory documents, and interpretation of fiqh books. The results showed that in positive law, extortion is categorized as a criminal act of corruption with severe criminal penalties under the Corruption Eradication Law, such as a minimum prison sentence of 4 years to a maximum of 20 years, and additional penalties such as fines. Meanwhile, in Islamic criminal law, extortion is categorized as jarimah ta’zir with flexible sanctions adjusted by the judge, such as dismissal from office or return of extortion proceeds, which aims to maintain the public interest. The comparison shows that positive law focuses on deterrent effects and system protection, while Islamic law emphasizes moral justice and restoration of community rights. This research contributes to offering an integrative approach that combines the power of positive law and the values of Islamic law, in order to eradicate extortion effectively and fairly.